A study of the effect of infection with the Corona virus on the D-Dimer rate in some patients in Brack Alshati city - Entesar Rammadan; Albashir M A Yhmed (Journal of Pure & Applied Sciences, 2023)
Background: Corona virus infection (Covid-19) is one of the most severe infections that spread at the end of the year 2019, and killed millions of people, especially the elderly. This virus infects the respiratory system and spreads and causes many symptoms and complications. Objective: The study aimed to know effect of virus on the D-dimer concentration, and compare these rates for patients after clinical and pharmacological treatment. Materials and Methods: blood samples were collected from patients those did not suffer from any chronic diseases such as high blood pressure, diabetes or other diseases that could cause an increase in the concentration of this protein. Their ages ranged between 35-70 years, and 25 samples of healthy people who did not suffer from any diseases were used as control samples. Dimers were measured for all samples. The results were analysed statistically using the Minitab16 statistical analysis program in order to find out the differences between healthy and patients before and after treatment. Results: The results of the study showed that, the concentration of D-dimer in patient group was 0.923 ± 0.124 micrograms/ml, while it was 0.1 micrograms / ml in control group. Statistically it was significant increase in D-dimer in patient group when compared to the control group (p≤0.05) , this rise was associated with the emergence of many symptoms. The results also showed that there were statistically significant differences between the concentration of dimer before treatment (0.942 ± 0.1 micrograms/ml) and its concentration after treatment (0.456 ± 0.09 micrograms / ml). Conclusion: The results of the study concluded that the Corona virus negatively affects the D-dimer rate, as its rate increases in patients, but clinical and pharmacological treatment leads to a decrease in its rate to the normal level compared to the treatment of infections caused by the virus.